Youth sports: What counts as "Positive development?" - Coakley, J. (Journal of Sport and Social Issues, 2011)
There is a widespread belief that sport participation inevitably contributes to youth development because sport`s assumed essential goodness and purity is passed on to those who partake in it. Promoted and perpetuated by sport evangelists and kindred spirits, this belief inspires the strategy of using sports to create among young people the attributes needed to achieve personal success. This neoliberal approach to development is perpetuated by anecdotes and unsystematic observations that uncritically support the evangelistic promise that sport participation produces positive development among young people. Although a few scholars in the sociology of sport have studied sport participation and identified conditions under which particular outcomes are likely to occur, there remains a need for critical research and theory that identifies the processes through which sport participation is or is not linked with subsequent forms of civic engagement and efforts to produce progressive change transcending the lives of particular individuals. Strategies for doing this are identified.